Safety and efficacy of fecal microbiota transplantation in the treatment of Parkinson’s disease: a systematic review of clinical trials - Chen, Kewei; Sun, Lirong; Liu, Yilan; Chen, Ran (Frontiers in Neuroscience, 2025)
IntroductionParkinson’s disease (PD) is the second most common neurodegenerative disease with limited treatment options and increasing incidence. The Microbiota–Gut–Brain Axis (MGBA) offers new insights for PD treatment, as gut microbiota imbalances are linked to PD. Fecal microbiota transplantation (FMT) shows potential to improve gut dysbiosis and has gained attention for PD treatment.MethodsWe conducted a review following PRISMA 2009 guidelines, searching PubMed, EMBASE, Web of Science, and Scopus up to December 1, 2024. We included clinical trials of FMT for PD patients, regardless of stage or type, with outcomes related to efficacy or safety. Non-clinical trials were excluded. Two investigators independently assessed studies, extracted data, and evaluated risk of bias and quality.ResultsA total of 1,147 articles were retrieved, and six studies involving 104 patients were included. Four were randomized controlled trials, one was a cohort study, and one was a case series. Patients had a mean age of 63.2 years and disease duration of 5.6 years. After FMT, some patients showed improvements in UPDRS scores, H-Y grades, NMSS scores, and constipation symptoms, but results varied across studies. No serious FMT-related adverse events occurred. Most were mild gastrointestinal issues. Gut microbiota diversity and beneficial bacterial abundance changed after FMT, correlating with clinical outcomes. FMT materials were mostly from unrelated donors with diverse preparation and delivery methods.DiscussionFMT shows efficacy and safety in PD treatment but is insufficient as a standard due to study heterogeneity and small sample sizes. Future research needs larger samples, unified tools, and standardized FMT procedures. Combining FMT with other therapies may improve efficacy.